Pandas - Barrett, Norman S. (London ; F. Watts, 1988)
Text and photographs introduce the giant panda in the wild and in captivity.
Includes index.
Keywords: Giant panda -- Juvenile literature; Pandas -- Juvenile literature; Giant panda; Pandas